Ending Extreme Poverty by 2030 : The Final Push - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the twin goals of ending extreme poverty by 2030 and boosting prosperity among the poorest 40 percent in low and middle-income countries. The strategy is summed up in three words: grow, invest, and insure. He talks about the need to be creative and use all of the resources to leverage much-needed private sector investment to build infrastructure and create jobs. He promises that the World Bank Group will continue to support governments and make investments in a broad variety of areas in the fight against extreme poverty in developing countries. He talks about empowering women through education for mothers to have healthier children, and, when they have financial resources, they’re more likely to invest in the next generation. He talks about the most effective ways to encourage investment in the extreme poor and improve health and educational service delivery, is accountability. He concludes by saying that the governments must be more accountable to citizens, and work to reduce arbitrary treatment at the hands of security forces and the demand for bribes from poor people which will help to minimize the likelihood of violent conflict and eliminate a driver of poverty.